Arquitetura para escalonamento oportunístico na nuvem com qualidade de serviço - Albuquerque, Caetano; Gama, Diego; Brito, Andrey (Companion Proceedings of the Brazilian Symposium on Computer Networks and Distributed Systems (SBRC); 2023: Companion Proceedings of the 41st Brazilian Symposium on Computer Networks and Distributed Systems, 2023)
The use of opportunistic computing on the cloud is popular due to enabling hosting batch processing applications at lower costs. However, this model does not guarantee availability, which restricts quality of service. Moreover, since prices fluctuate frequently, high priority on optimal availability requires low priority on cost savings. This paper proposes a modular opportunistic auto-scaler for Kubernetes that balances opportunistic node costs and processing delay to ensure quality of service. Based on prices from 2021 AWS, the solution provided up to 50% savings when comparing to on-demand prices, thus allowing near-realtime processing.